2021
DOI: 10.1155/2021/9615429
|View full text |Cite
|
Sign up to set email alerts
|

Tea Polyphenols Enhanced the Antioxidant Capacity and Induced Hsps to Relieve Heat Stress Injury

Abstract: Keap1-Nrf2-ARE and heat shock proteins (Hsps) are important endogenous protection mechanisms initiated by heat stress to play a double protective role for cell adaptation and survival. H9C2 cells and 80 300-day-old specific pathogen-free chickens were randomly divided into the control and tea polyphenol groups and used to establish a heat stress model in vitro and in vivo. This task was conducted to explore the protection and mechanism of tea polyphenols in relieving thermal injury. A supplement with 10 μg/mL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…By improving the activity of the ALP enzyme, it helps to increase the feed intake of the pigs [ 36 ]. T-AOC, SOD, and GSH-Px are important indicators that reflect the body’s antioxidant level, also known as the body’s antioxidant enzyme system [ 37 ]. Among them, GSH-Px catalyzes peroxides to produce alcohol or water through a reduction reaction.…”
Section: Discussionmentioning
confidence: 99%
“…By improving the activity of the ALP enzyme, it helps to increase the feed intake of the pigs [ 36 ]. T-AOC, SOD, and GSH-Px are important indicators that reflect the body’s antioxidant level, also known as the body’s antioxidant enzyme system [ 37 ]. Among them, GSH-Px catalyzes peroxides to produce alcohol or water through a reduction reaction.…”
Section: Discussionmentioning
confidence: 99%
“…That is, exposure to extreme heat acts as a stimulus, triggering the activation and accumulation of HSP to protect functional proteins from degeneration ( 34 ). In the study, after 0,.5, and 2 h heat treatment, the level of HSP70 in the H9C2 cells was significantly higher than that in the normal temperature control group ( 30 ). This is consistent with our findings that HSP70 levels were significantly elevated after HS treatment and HSP70 levels were reversed to normal by ACP.…”
Section: Discussionmentioning
confidence: 73%
“…Keap1-Nrf2 and HSPs are important endogenous protective mechanisms of HS initiation, participating in the regulation of antioxidant enzymes and playing a dual protective role in cell adaptation and survival ( 30 ). Nrf2 is a key factor in the Keap1-Nrf2 pathway, which plays an important role in activating antioxidant signaling pathways to prevent oxidative stress-induced cell and tissue damage and to maintain redox balance ( 31 ); it can also boost the production of other antioxidants ( 32 ); Keap1 is a negative regulator of Nrf2 ( 33 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…The potential of polyphenols in the prevention of excessive ROS production is interesting with regard to increased antioxidant enzyme production and in the regulation of heat shock proteins (HSPs). Both are associated with cytoprotection, as shown by Yin et al [ 90 ]. Antioxidant genes are upregulated in order to convert the superoxide anion radical to H 2 O 2 (e.g., SOD1) or they are involved in modulating of glutathione homeostasis (e.g., GPX1, GPX2, and CAT) [ 91 ].…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, another study showed reduced HSP70 expression in organs after longer period (6 h) of transportation stress, thus suggesting a certain adaptability to the expression of this gene [ 94 ]. The role of polyphenols in the presence of heat stress and their potential in stimulation of HSPs was explored in chickens by Yin et al [ 90 ], who showed no clear direction of effects of tea-derived phenolic compounds on different HSPs in the presence of heat stress. The results from our analyses in the liver, without changes in the expression of HSP70 and HSP90AA1 by the diets, suggest an absence of acute stress on day 27/28 and day 55/56 that could allow polyphenols to alleviate the expression of these genes.…”
Section: Discussionmentioning
confidence: 99%